Candesartan cilexetil in cardiovascular prevention - A. Ya. Ivleva (Кардиоваскулярная терапия и профилактика, 2007)
Effectiveness and good tolerability of angiotensin receptor antagonists (ARA) in arterial hypertension (AH) have been demonstrated in large-scale randomized clinical trials. Substantial pharmacodynamic differences between various ARA, potentially playing important clinical roles, were identified. Candesartan benefits in regard to stage and duration of blood pressure (BP) reduction, as well as cardiovascular event risk reduction, were shown for long-term AH treatment with the agent. Metabolic benefits of candesartan, independent of BP reduction, were observed in diabetic patients. Candesartan is also effective in chronic heart failure, combined with beta-adrenoblocker, or with beta-adrenoblocker and ACE inhibitor.